2010
DOI: 10.3198/jpr2009.07.0413crg
|View full text |Cite
|
Sign up to set email alerts
|

Registration of Three Soybean Germplasm Lines Resistant to Phakopsora pachyrhizi (Soybean Rust)

Abstract: Soybean rust, caused by Phakopsora pachyrhizi Sydow, is one of the most important foliar diseases of soybean [Glycine max (L.) Merr.]. Development of rust‐resistant lines is one objective of many soybean breeding programs. Three soybean germplasm lines designated as TGx 1987–76F (Reg. No. GP‐369, PI 657702), TGx 1987–118F (Reg. No. GP‐370, PI 657703), and TGx 1987–129F (Reg. No. GP‐368, PI 657701) with resistance to P. pachyrhizi and to Xanthomonas axonopodis pv. glycines (Nakano) Vauterin, Hoste, Kersters & S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The cultivar has been reported to consistently confer resistance against soybean rust in Nigeria , the United States , and Uganda . Cultivar UG5 has been deployed in breeding programs in Nigeria and Uganda (Paul et al, 2010;) and appears to be effective as was observed among the African isolates in our study. Despite its effectiveness, isolates from Argentina induced susceptible reactions on this cultivar, suggesting the presence of a more virulent population in South America.…”
Section: Isolate Infection Types On Soybean Differentialssupporting
confidence: 71%
“…The cultivar has been reported to consistently confer resistance against soybean rust in Nigeria , the United States , and Uganda . Cultivar UG5 has been deployed in breeding programs in Nigeria and Uganda (Paul et al, 2010;) and appears to be effective as was observed among the African isolates in our study. Despite its effectiveness, isolates from Argentina induced susceptible reactions on this cultivar, suggesting the presence of a more virulent population in South America.…”
Section: Isolate Infection Types On Soybean Differentialssupporting
confidence: 71%
“…SBR‐resistant breeding lines have been developed in the United States (Boerma et al, 2011; Diers et al, 2014; King et al, 2016b; Paul et al, 2010). It is thought that more durable and broader resistance can be achieved by pyramiding two or more Rpp genes (Childs et al 2018a; Yamanaka & Houssain, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With the discovery of soybean rust in the United States in 2004, more effort was placed on field screening of PIs and genetic studies in the United States. These evaluations led to the development and release of soybean rustresistant germplasm Diers et al 2013;Paul et al 2010). Although there are no commercially available soybean cultivars with soybean rust resistance in the United States, these early releases and breeding lines that are being evaluated will lead to cultivar releases in the near future, including some with at least two Rpp genes.…”
Section: Soybean Rust Managementmentioning
confidence: 99%